A remark on the Hadamard-Hirakawa formula for an electromagnetic cavity problem - Zaccaron, Michele (Bollettino della Unione matematica italiana (2008), 2024)
In this paper we consider the eigenvalues of time-harmonic Maxwell’s equations in an electromagnetic cavity subject to a regular variation of the domain, described via a deformation function on the boundary. We show the direct equivalence of two Hadamard-type perturbation formulas for the shape derivative of simple eigenvalues.